"It's not just me on a video call with someone"¦" Students' experiences of a forced transition from face-to-face psychotherapy to online psychotherapy during COVID-19: an interpretative phenomenological analysis - Keet, Nicole Tahnee (Rhodes University, Faculty of Humanities, Department of Psychology)
The aim of this study is to explore university students' experience of a forced transition from face-to-face therapy to online therapy during COVID-19. This pandemic was unexpected and affected all areas of life, including the closure of universities, which left therapists and clients alike unsure of how to navigate these unchartered territories. Although there is a considerable amount of international research on experiences of online therapy, there is little research on a forced transition to online therapy because of COVID-19 and even less within the South African context. A sample of six participants between the ages of 20 and 30 years old were selected through purposive and convenience sampling. Semi-structured interviews were conducted, and interpretative Phenomenological Analysis (IPA) was utilised to ascertain how participants make sense of their worlds in relation to the transition to online therapy. The analysis provided three main superordinate themes, which are supported by subordinate themes. The superordinate themes are: 1) Online therapy as authentic and continuous, where the participants experienced the comfort and convenience of online therapy, the continuity of care and the anonymity of online therapy. 2) Online therapy as disruptive and invasive, where participants experienced issues with privacy, an intrusive environment, technological challenges, lack of body language and therapy feeling more disposable. 3) Getting used to online therapy with some help from the therapist, where participants felt an adjustment period was necessary as well as transparency and containment from the therapist to help with the transition. These findings support some existing South African literature; however, it also engages with findings unique to this study, that will hopefully be used for further exploration. The study ends with recommendations for training therapists on using online therapy.
Keywords: Online therapy; COVID-19 Pandemic, 2020- -- Influence; Interpretative phenomenological analysis; Psychologists -- Training of; College students -- Attitudes